2015
DOI: 10.1186/s11671-015-0880-9
|View full text |Cite
|
Sign up to set email alerts
|

Conductive-bridging random access memory: challenges and opportunity for 3D architecture

Abstract: The performances of conductive-bridging random access memory (CBRAM) have been reviewed for different switching materials such as chalcogenides, oxides, and bilayers in different structures. The structure consists of an inert electrode and one oxidized electrode of copper (Cu) or silver (Ag). The switching mechanism is the formation/dissolution of a metallic filament in the switching materials under external bias. However, the growth dynamics of the metallic filament in different switching materials are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…Yazdanparast et al [52] reported the 70-nm CF diameter using a Au/Cu 2 O 3 /Au structure at a CC of 10 mA. According to our previous report [3], the CF diameter is approximately 70 nm in a Cu/GeO x /W structure at a CC of >1 mA. A larger diameter of 2 μm using a Pt/CuO/Pt structure was reported by Yasuhara et al [53].…”
Section: Resultsmentioning
confidence: 99%
“…Yazdanparast et al [52] reported the 70-nm CF diameter using a Au/Cu 2 O 3 /Au structure at a CC of 10 mA. According to our previous report [3], the CF diameter is approximately 70 nm in a Cu/GeO x /W structure at a CC of >1 mA. A larger diameter of 2 μm using a Pt/CuO/Pt structure was reported by Yasuhara et al [53].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Even different switching materials such as HfO 2 O 3 9 have been reported, however GdO x has been reported a few. [10][11][12][13] To achieve 3D high-density architecture, cross-point memory is one of the best solutions.…”
mentioning
confidence: 99%
“…Further study is needed to control Cu diffusion as well as filament diameter or RESET current could be controlled. Obviously, if the LRS value is low, then the RESET voltage will be also small; especially RESET voltage for the CBRAM devices is small [1]. A large resistance ratio of >10 5 is observed because of higher RESET current.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, the erase operation can be controlled by external current (> I RESET ) and voltage (< V RESET ). However, the RESET operation will have also high-speed operation of few nanoseconds [1]. So, external light impacts the device switching, which is also very useful for a new area of research.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation